What kind of innovations do we need to secure our future? - Ulrich Witt (Journal of Open Innovation: Technology, Market, and Complexity, 2016)
The question of what kind of innovations can secure our future is in this paper put in perspective with the unknown risks which innovations may imply. Innovations sometimes turn out to cause severe negative externalities after they have successfully passed the market test. In such cases, the social costs that are revealed only later may result in substantial welfare losses. Obviously, innovations of this kind are the opposite of what is needed. Can the knowledge flows related to innovation processes be strategically arranged in such a way that these externality risks are minimized? The options to be reviewed relate to the debate on open vs. closed innovation processes initiated in management science. The paper briefly discusses several aspects of this debate and introduces a model of self-organizing belief formation which reflects the conditions of open vs. closed innovation processes. On this basis it is shown that a conflict arises between arrangements fostering an early discovery of negative externalities of innovations and the incentives potential innovators have to pursue innovative activities.
Keywords: 650